Attitudes towards the Use of the Achievement File as an Alternative Assessment Tool in Schools of South of Nablus - Palestine - Jayousi , Majdi (Dirasat: Educational Sciences, 2020)
This study aims to identify the relationship between teachers' attitudes towards using the achievement file as an alternative assessment tool in south of Nablus – Palestine schools. Furthermore, the differences in the study sample's attitudes towards using the achievement file as an alternative assessment tool according to the variables (age, educational qualification and experience years). The researcher used the descriptive analytical approach on a sample of (523) male and female teachers from south of Nablus - Palestine schools, who were selected in a stratified manner. The researcher also used the questionnaire as a tool for the study, which consisted of three fields and (30) paragraphs. To address the responses of the study sample, frequencies and percentages, means and standard deviations, Cronbach's alpha equation, one-sample t-test, independent groups t-test and One Way ANOVA were used. The results of the study showed that there were statistically significant differences at the level of (a≤0.05) in teachers' attitudes toward using the achievement file as an alternative assessment tool in the south of Nablus schools due to the variables (gender, age, academic qualification and experience years). The study recommends moving from the traditional evaluation and implementing the achievement file as an alternative assessment tool in primary and secondary schools.